Neural structural correlations of Mind Wandering in patients with schizophrenia (2022)
It has been proposed that Mind Wandering (MW) is a possible neural and biological mechanism associated with the positive symptoms of schizophrenia. Nevertheless, the evidence regarding this issue is contradictory and insufficient to determine the association. That is why this study's aim is to explore MW in patients with schizophrenia in comparison to healthy controls by using an experimental task (Experience Sampling Test) and additionally exploring the neural structural correlations between its results and MRI scans. For this aim, we assessed 43 participants, 24 patients and 19 controls, who did the experimental task. A subsample of 34 participants, 20 patients and 14 controls, conducted MRI scans. The Experience Sampling Test consisted in doing one of the two following tasks aleatorily: (1) saying every word they thought of that start with the presented letter; (2) Mentioning every idea and thought they had during the previous task, but that were not related to the task. Then, from the first task we obtained a performance rate for every participant and with the answers from the second task and the help from 5 experts, we determined: (1) the presence of MW, (2) the category and content of the thoughts, (3) the tense in which the thoughts were centered and (4) the connection between the different thoughts. In addition to this, we obtained the Kappa's Fleiss and voxel-based morphometry (VBM) to explore the associations between the performance rate, the presence of MW and the connection of the thoughts. We also applied cognitive and clinical assessments to evaluate the cognitive state and the presence of various symptoms of depression, anxiety, mania, and positive symptoms of schizophrenia. The behavioral results showed no significant differences between patients and controls in any experience sampling scales. Nevertheless, in the performance rate, control said significantly more words than patients. Regarding the VBM results, for all the participants in the MW presence, we found positive correlations in the inferior temporal gyrus and the insula, for connection in the superior, medial, and inferior temporal gyrus and a negative association between performance and volumes in the cerebellum and inferior temporal gyrus. Only for the patients, we found positive correlations between volume and MW presence un the superior (dorsolateral and medial) frontal gyrus and with the performance rate we found a negative correlation with the volume of the left frontal gyrus (triangular and medial) and the nucleus caudate. To conclude, the results indicate that there are no significant differences between groups in the presence, content, tense, and connection of MW, but there were some specific neural correlates. These results contribute to a mayor comprehension of MW in schizophrenia and suggest that MW is not the biological phenomena underlying the positive symptoms of schizophrenia patients.